Interpretive Trail for Elementary School children: use of playful, sensory and cultural situations in Caçu, Goiás, Brazil (Research, Society and Development, 2022)
Environmental Education is an efficient instrument in the educational process, with a view to involving the school community and raising awareness in people's environmental education. In this perspective, the objective of this research was to implement an interpretive trail with the use of playful, sensory and cultural situations for elementary school children in the Municipal Lake of Caçu, Goiás. The Interpretative Trail route was carried out with a target audience consisting of 17 children from 7 to 8 years old, from one of the classes of the 2nd year of Elementary School, in the afternoon shift at Escola Municipal Olívio Girotto, with the monitoring of the teacher and a monitor of the class. Along the Interpretative Trail, a sequence of playful-pedagogical, educational and recreational activities was planned, covering themes related to the environment and its conservation. The path of the Interpretative Trail by the target audience lasted an hour and the children were interested and curious about the environment that surrounded them all the time. After the visit, changes in the behavior of the target audience were observed, as evidenced by reports and drawings of observations of nature and changes in attitude towards situations of environmental conservation. This shows the importance of awakening children's curiosity about nature and sharpening their eyes both to ecological phenomena and to the environmental impacts resulting from anthropic actions, using the Interpretative Trail as a socio-educational tool.